Stability and thermal conductivity enhancement of carbon nanotube nanofluid using gum arabic - Rashmi, W.; Ismail, A.; Sopyan, I.; Jameel, A.; Yusof, F.; Khalid, M.; Mujawar, Mubarak (Taylor & Francis, 2011)
This experimental study reports on the stability and thermal conductivity enhancement of carbon nanotubes (CNTs) nanofluids with and without gum arabic (GA). The stability of CNT in the presence of GA dispersant in water is systematically investigated by taking into account the combined effect of various parameters, such as sonication time, temperature, dispersant and particle concentration. The concentrations of CNT and GA have been varied from 0.01 to 0.1 wt% and from 0.25 to 5 wt%, respectively, and the sonication time has been varied in between 1 and 24 h. The stability of nanofluid is measured in terms of CNT concentration as a function of sediment time using UV-Vis spectrophotometer. Thermal conductivity of CNT nanofluids is measured using KD-2 prothermal conductivity meter from 25 to 60°C. Optimum GA concentration is obtained for the entire range of CNT concentration and 1-2.5 wt% of GA is found to be sufficient to stabilise all CNT range in water. Rapid sedimentation of CNTs is observed at higher GA concentration and sonication time. CNT in aqueous suspensions show strong tendency to aggregation and networking into clusters. Stability and thermal conductivity enhancement of CNT nanofluids have been presented to provide a heat transport medium capable of achieving high heat conductivity. Increase in CNT concentrations resulted in the non-linear thermal conductivity enhancement. More than 100-250% enhancement in thermal conductivity is observed for the range of CNT concentration and temperature.